2011
DOI: 10.1299/jee.6.69
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Shedding from Tube Banks with Closely Mounted Serrated Fin

Abstract: This paper focuses on the vortex shedding from tube banks with closely mounted serrated fin. The tube banks were installed rigidly in the test section of a wind tunnel. We measured the mean velocity, the velocity fluctuation spectrum, and the gap velocity in the model tube banks that had the same pitch ratio as a boiler heat exchanger. We found two types of vortex shedding with different Strouhal numbers S t of 0.40 and 0.20 in the case of Reynolds numbers R e in the range 2.8 × 10 4 to 6.2 × 10 4. Strouhal nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The characteristics of vortex shedding from tube banks with closely mounted serrated fin was investigated in [1] where the relationship between the Strouhal number defined by the equivalent diameter as the characteristic length of a finned tube in the tube banks and the Strouhal number map for bare-tube banks was examined. Whereas in [2] the author has presented various outlet conditions of a shell and tube heat exchanger theoretically and experimentally in which it is observed that prime parameter geometry of outlet affects the performance, maintenance and life span of a vertical shell and tube evaporator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of vortex shedding from tube banks with closely mounted serrated fin was investigated in [1] where the relationship between the Strouhal number defined by the equivalent diameter as the characteristic length of a finned tube in the tube banks and the Strouhal number map for bare-tube banks was examined. Whereas in [2] the author has presented various outlet conditions of a shell and tube heat exchanger theoretically and experimentally in which it is observed that prime parameter geometry of outlet affects the performance, maintenance and life span of a vertical shell and tube evaporator.…”
Section: Introductionmentioning
confidence: 99%
“…In this proposed work design, development & testing of STHE is carried out. Along with the parameter considered in [1][2][3][4][5][6][7][8], vibration analysis is performed to optimized unsupported span of tube by using HTRI software. Detail overview on work carried out by researchers is presented in Section 1, Section 2 & 3 states mechanics of flow-induced vibration and the current problem definition & objective, details of STHE is given in Section 4.…”
Section: Introductionmentioning
confidence: 99%